(untitled) (Research, Society and Development, 2020)
The prescription consists of a written order, directed to the pharmacist, which tells how the medicine should be given to the patient. Infectious diseases account for most of the morbidity leading to medical appointments and hospitalizations. In view of this, antibiotics are a widely prescribed group of drugs. The objective of the study is to analyze the profile of antibiotic prescriptions, listing the most prescribed ones, analyzing the most used classes and identifying the most frequent diseases. A retrospective, cross-sectional and quantitative study was carried out on the use of drugs from data collected in the CCIH system, from a private hospital in Teresina -I, with 77 beds. The information obtained was issued in the period from May to June of 2018, intended for all sectors of the hospital. Regarding the results, 81 prescriptions were analyzed, in which Cefepime 12.3 (n = 10) was analyzed; Vancomycin 11.1% (n = 9); Ceftriaxone 9.9% (n = 8); the most prevalent therapeutic class in the study was beta-lactams (47%), and the most prevalent diagnoses in the study were pulmonary diseases (28). Thus, it is concluded that beta-lactams are the most prescribed antibiotics, as well as it was possible to determine pulmonary diseases as the most affected in that period of time.